2021
DOI: 10.1097/gme.0000000000001729
|View full text |Cite
|
Sign up to set email alerts
|

Early and surgical menopause associated with higher Framingham Risk Scores for cardiovascular disease in the Canadian Longitudinal Study on Aging

Abstract: Objective: In women, the risk of cardiovascular disease (CVD) is higher in the postmenopausal period. The effect that menopausal type, natural versus surgical, or the age at natural menopause has on CVD needs further investigation. To this end, we assessed the association between menopausal type and timing and the 10-year office-based Framingham Risk Score (FRS) in women from the Canadian Longitudinal Study on Aging. Methods: We included women aged 45 to 85 years from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In our study, both early and late menopausal ages were associated with higher FRS, and the associations varied by parity. Our results were generally consistent with a cross-sectional study of the Canadian Longitudinal Study on Aging, which showed that early menopause was associated with higher FRS 31 . Other previous studies 8-11 also showed that early menopausal age was associated with higher risk of CVD, whilst late menopause was associated with a higher risk of hemorrhagic stroke in a prospective study of the Korean Elderly Pharmacoepidemiologic Cohort 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, both early and late menopausal ages were associated with higher FRS, and the associations varied by parity. Our results were generally consistent with a cross-sectional study of the Canadian Longitudinal Study on Aging, which showed that early menopause was associated with higher FRS 31 . Other previous studies 8-11 also showed that early menopausal age was associated with higher risk of CVD, whilst late menopause was associated with a higher risk of hemorrhagic stroke in a prospective study of the Korean Elderly Pharmacoepidemiologic Cohort 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results were generally consistent with a cross-sectional study of the Canadian Longitudinal Study on Aging, which showed that early menopause was associated with higher FRS. 31 Other previous studies [8][9][10][11] also showed that early menopausal age was associated with higher risk of CVD, whilst late menopause was associated with a higher risk of hemorrhagic stroke in a prospective study of the Korean Elderly Pharmacoepidemiologic Cohort. 12 In our study, women with later menopausal age had higher prevalence of diabetes and hypertension, and were therefore more prone to develop CVD.…”
Section: Discussionmentioning
confidence: 84%
“…3,[32][33][34] Given the role of surgical management in endometriosis, it was not surprising that, in our population, more patients with endometriosis had hysterectomies, oophorectomies and pre mature ovarian insufficiency than those in the unexposed group. As previously shown in the Women's Health Initiative cohort, 35 and the Canadian Longitudinal Study on Aging (CLSA), 36 females who eventually undergo a hysterectomy have been shown to have a worse cardiovascular risk profile and higher incidence of CVD. This supports other studies that suggested hysterectomy and oophorectomy among younger females with endometriosis may increase the risk of coronary heart disease.…”
Section: Discussionmentioning
confidence: 73%
“…Evidence that estrogen/s may be protective comes from our finding that women with cardiomyopathy and early menopause had higher sST2 levels ( Figure 5 ) indicating that estrogen may reduce sST2 levels. A recent study found that women with early or surgical menopause had higher Framingham Risk Scores for CVD than those with normal menopause ( 48 ). But other factors may contribute to age-related changes in sST2 in men and women such as shifts over time in mitochondrial function, which has been associated with HF ( 49 ).…”
Section: Discussionmentioning
confidence: 99%